Is Extreme in the Eye of the Beholder? An Experimental Assessment of Extremist Cognitions - Shortland, Neil D. (Journal of interpersonal violence, 2022)
Scholars have extensively discussed the topic of ?online radicalization,? often seeking to understand the form and function of online extremist material. However, this work has neglected to examine the role that the Internet plays alongside individual personality factors in the process through which someone develops violent extremist cognitions. This article aims to extend the understanding of the role of personality differences in the effect of exposure to extremist material online. In this study, we experimentally measure the short-term psychological consequences of exposure to extremist material on extremist cognitions. We use a between-group experimental design in which participants are shown extremist propaganda with either pre- or post-counter messages. Our results indicate that trait personality, and specifically aggression, may be more influential than exposure to extremist propaganda in influencing extremist cognitions. We discuss the implications of these results in the context of future research directions.